Dental Visit, Dental Diseases, and Dental Therapist Pattern in The Implementation of NHI at Private Clinics - Afina Hasnasari Heningtyas; Iwan Dewanto (Indonesian Dental Association, 2019)
Introduction: Since 2014 through the National Health Insurance (JKN) program, the pattern of health financing in Indonesia has been changed, in the first level health facilities (FKTP), from the fee for service payment to capitation payments system. Reports from the Public Health Office of Yogyakarta City showed that in 2014 there was an increased in basic dental services in the city of Yogyakarta by 68.01% from 2013. The Firdaus Pratama Clinic Yogyakarta is a primary clinic with medical and dental services as one of the providers of the JKN program since 2015. Objective: The purpose of this study was to evaluate the implementation of the national health insurance program in dentistry at Firdaus Pratama Clinic, Yogyakarta. Methods: The type of this research was descriptive observational study, with the method used in the form of secondary data observation. Secondary data was obtained through electronic medical records at Firdaus Pratama Clinic. This research was conducted at the Firdaus Pratama Clinic in Yogyakarta which has been working with BPJS since 2015. Results: The number of participants and the number of dental visits at the Firdaus Pratama Clinic continued to increase. The 3 diagnoses in dental services at the Firdaus Pratama Clinic that frequently found in the form of consultation were necrosis of pulp, dental caries, and pulpitis. Conclusion: The category of dental visits at Firdaus Pratama Clinic was high, which found more than 2% utilization based on the number of participants and dental visits